(untitled) - Lowitt, Eric (New York, 2011)
The Future of Value reveals what it takes for companies to grow and outperform the competition in today's growth-constrained, sustainability conscious world.
Keywords: Management,Strategic planning,Value,Quản lý,Kế hoạch chiến lược,Đánh giá; Environmental aspects,Environmental aspects,Lĩnh vực môi trường,Lĩnh vực môi trường